Proceedings of IEEE Symposium on Autonomous Underwater Vehicle Technology (AUV'94)
DOI: 10.1109/auv.1994.518646
|View full text |Cite
|
Sign up to set email alerts
|

Toward an improved understanding of thruster dynamics for underwater vehicles

Abstract: IntroductionThis paper proposes a novel approach to As the use of Remotely Operated modeling the four quadrant dynamic response Underwater Vehicles becomes more of thrusters as used for the motion control of widespread and their tasking more complex ROV and AUV underwater vehicles. The in deeper waters, there is a need to free the significance is that these vehicles are small in vehicle from the power and signal tether, and size and respond quickly to commands.to increase both the level of control autonomy Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
2
2

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 2 publications
3
73
2
2
Order By: Relevance
“…The authors tested the performance of the thruster in three different operating modes, namely, forward travel, low speed manoeuvring, and high speed turning. The basis model used was similar to that developed in (1) (Healey et al, 1995). It was found that the dynamic performance of the thruster was not significantly altered by the operating mode of the vehicle, however the steady state performance was affected.…”
Section: Previous Modelling Approaches For Tunnel Thrustersmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors tested the performance of the thruster in three different operating modes, namely, forward travel, low speed manoeuvring, and high speed turning. The basis model used was similar to that developed in (1) (Healey et al, 1995). It was found that the dynamic performance of the thruster was not significantly altered by the operating mode of the vehicle, however the steady state performance was affected.…”
Section: Previous Modelling Approaches For Tunnel Thrustersmentioning
confidence: 98%
“…These relationships are combined with a model of the motor and blade element relations such that an example model can be summarised as (Healey et al, 1995):…”
Section: Modeling Approaches For Underwater Thrustersmentioning
confidence: 99%
“…In later works [2,10,12], more accurate models employing lift and drag curves, and that also incorporate some However, considering recent experimental results, marine thrusters may also exhibit non-smooth nonlinearities such as dead-zones. A dead-zone is a hard nonlinearity, frequently encountered in many industrial actuators, and its presence can drastically reduce control system performance and lead to limit cycles in a closed-loop system.…”
Section: Dynamic Thruster Modelmentioning
confidence: 99%
“…Many of these works [12,[25][26][27] address the problem of the influence of thruster dynamics on overall vehicle behaviour, and the importance of considering this effect in the dynamic positioning system. Traditionally, some mathematical models of the thruster are used directly to estimate, in a feed-forward manner, the required voltage (or current) to produce the desired thrust force.…”
Section: Introductionmentioning
confidence: 99%
“…The precision and complexity of the required tasks need an increase of the maneuvering accuracy and the propulsion system plays a key role in the achievement of the missions. Thruster modeling and control has been subject to a growing interest in the last years (Yoerger et al 1990), (Healey et al 1995), (Whitcomb and Yoerger 1995), (Fossen and Blanke 2000), (Bachmayer et al 2000), (Smogeli 2006) and (Pivano et al 2007). The primary objective of low level thruster control is to obtain the desired thrust from the propeller regardless the environmental state.…”
Section: Introductionmentioning
confidence: 99%